Analyse conversationnelle et didactique de la traduction - Stefanink, Bernd (Studia Romanica Posnaniensia, 2007)
The analysis of conversations held by two or more students negotiating a joint version of a translation has an important didactic value. It enables the teacher to work on the translational behavior of the students instead of merely limiting her/his activity to the correction of diverse grammar and semantic mistakes. The confrontation with their own translation procedures heightens the students’ awareness of what it really means to translate. In many cases it leads to a catharsis which in turn motivates the students to study the different factors involved in the translation process. On a larger scale, conversational analysis provides the teacher with a sound basis on which to structure a translation course and organize a syllabus.